ELECTROPHYSICAL PROPERTIES OF NANOFILMS - Dovranov, K.T.; ormuradov, M.T.; Ulashov, A.A.; Doniyorova, I. (Educational Research in Universal Sciences, 2023)
Manganese silica thin films of different thicknesses were obtained in a magnetron device under high vacuum conditions. The surface resistance, surface concentration and Hall coefficients of nanosized manganese silicide films obtained by the ion-plasma method were measured on an HMS 5000 device. The Hall coefficient for a 102.3 nm thick film of manganese silicide grown on a silicon surface by the ion-plasma method is 2,8979·10-5 sm3/C.